EFFECTS OF DELEGATION OF AUTHORITY ON ORGANIZATIONAL PERFORMANCE: A CASE OF TWIGA CHEMICAL INDUSTRIES LTD - KENNEDY, SHIKAMI AKWEYU; Keino, Dinah (European Journal of Business and Strategic Management, 2017)
Purpose:The purpose of this study was to investigate the effects of delegation of authority on organizational performance: a case of Twiga chemical industries ltd. Methodology:The study adopted adescriptive research design and correlation research design.The target population in this study was200 permanent employees of Twiga chemical industries ltd in Nairobi. Stratified sampling technique was used in this study to come with a desirable sample. Primary data was collected by use of questionnaires and utilized in this study to enhance originality of the study. The questionnaires were administered to the randomly selected employees who were the respondents. The questionnaire comprised of the questions that intended to answer the questions formulated with reference to the objectives of the study.The study used the quantitative method of data analysis. The collected data was edited, coded, keyed in and analysed using Statistical Package for Social Sciences (SPSS) version 20. The quantitative data wasanalysed using both descriptive statistics and correlations. Regression model was then used to show the relationship between independent variables and dependent variable. Results: Regression of coefficients results showed that legislative delegation and organisation performance are positively and significant related at both 1% and 5% confidence level (B=0.284, p=0.032). The results further indicated that adjudicative delegation and organisation performance are positively and significant related at 1% and 5% confidence level (B=0.319, p=0.011). The results further established that monitoring and enforcement delegation were positively and significantly related at 1% and 5% confidence level (B=0.334, p=.013). Similarly, results showed that agenda setting delegation and organisation performance were positively and insignificantly related at 5% confidence level (B=0.094, p=0.455). Unique contribution to theory, practice and policy: Based on the findings the study recommended that organisations and firms should consider delegation of authority as one way of enhancing organisation performance. The study further recommended that those in authority should be very careful when delegating authority not to go overboard.